Electric motor internal heat convection modelling and analysis: Electric motor internal heat convection modelling and analysis - Kumar, Anil (My University, 2018)
An electrified vehicle is a complex thermal environment including a number of components such as electric machines, converters and chargers, which require cooling to function optimally. If the cooling is insufficient, the losses will increase, the performance of the system will be lowered and the life span of the components might be compromised. Currently, the trend to carry out thermal analysis of electric motors is increasing, so as to improve the performance of the machines. In this thesis, the heat transfer through internal parts of a specific permanent magnet synchronous electric motor (PMSM) is investigated. This type is typically used in hybrid vehicles or fully electric zero emission vehicles. Varying degrees of geometric complexities was studied. First, a simplified model version of the PMSM was constructed using the pre-processing software ANSA. The numerical analysis of the flow field and heat transfer was done in StarCCM+ which was used as a solver to model and simulate the air flow inside the electric motor. Here, we determine and investigate the dependency of the convective heat transfer coefficients and temperature on the rotational speed of the rotor inside the electric motor. In order to reduce the computational effort and time, a 1/8th section of the simplified motor model was also constructed. The difference in the results obtained from the 1/8th motor model case and the full simplified motor case was investigated. Second, a more complex ERAD (electric rear axle drive) PMSM model was constructed to conduct a conjugate heat transfer analysis. Additional geometric complexities was added compared to the simplified version like the addition of the cooling jackets in the housing part of the electric motor. An investigation of the convectional heat transfer coefficients and temperature distribution on the internal parts of the motor was made with full geometric details with respect to the operating speed of the motor. Furthermore, the coolant flow rate and operating temperatures of the coolant were varied, and investigations were done on how the convectional heat transfer coefficients and temperature of the coolant changes. Lastly, the temperature values obtained from the ERAD motor were compared with a preliminary reference lumped parameter thermal network (LPTN) model. Here, we noticed a large deviation in the results (higher than +/- 5 C) near the rotor region which is why further investigation in validation of the heat transfer coefficients are necessary. It was concluded from the above investigations that the obtained convective heat transfer coefficients are very sensitive to the fluid temperature used. Furthermore, the temperature and the heat transfer coefficients of the internal parts of the electric motor increase with motor speed.
Keywords: Strömningsmekanik; Grundläggande vetenskaper; Hållbar utveckling; Transport; Fluid mechanics; Basic Sciences; Sustainable Development; Transport